Survey personal and disease characteristics of children with‏ ‏Cancer hospitalized ‎in ‎‏17‏‎ Shahrivar hospital,‎‏ ‏Rasht - mahshid mirzaie; fatemeh yazdi; zahra navidi (Guilan University of Medical Sciences, 2009)
Introduction: Cancer is one of child diseases that has an incidence of ‎‏129‏‎ in ‎‏1‏‎ million ‎children and is still second reason for death of ‎‏1-14‏‎ years old children. The children who died ‎because of cancer lost an average of ‎‏69.5‏‎ years of life time. Therefore, identification of ‎personal and disease characteristics may be a way for facilitating cancer prevention in ‎children. ‎ Objective: This study was conducted to determine personal and disease characteristics of ‎children with cancer.‎ Methods: This descriptive study was conducted on ‎‏80‏‎ children with cancer hospitalized in ‎oncology ward of ‎‏17‏‎ Shahrivar Hospital in Rasht between Farvardin ‎‏1380‏‎ to Esfand ‎‏1384‏‎ ‎which was selected by convenience sampling. Data collection instrument consisted of two ‎parts questionnaire including demographic and disease characteristics. Data were collected by ‎observation and documentation of patients records and analyzed by SPSS software. ‎ Results: The finding showed that majority of children was ‎‏5-9‏‎ years old (‎‏47‏‎.‎‏25%‏‎), boy (‎‏60%‏‎), ‎was born with NVD (‎‏97‏‎.‎‏5%‏‎), and was city resident (‎‏65%‏‎). ‎‏72‏‎.‎‏5‏‎ percent of parents had ‎‏1-2‏‎ ‎children. The majority of samples had fathers with Diploma (‎‏57‏‎.‎‏5%‏‎) that half of them were ‎worker. Also majority of hospitalized children had ALL (‎‏53‏‎.‎‏75%‏‎) and Lymphoma (‎‏11‏‎.‎‏25%‏‎). ‎Only ‎‏7‏‎.‎‏5‏‎ percent of them mentioned a positive familial history of cancer. ‎‏48‏‎.‎‏25‏‎ percent of ‎children hospitalized between ‎‏1-9‏‎ times and the majority (‎‏32‏‎.‎‏5%‏‎) of them had intra spine ‎chemotherapy for ‎‏0-5‏‎ times. ‎‏45‏‎ percent of children died by the time sampling done. ‎ Conclusion: This research showed that Hematologic cancers had highest incidence that have ‎high mortality rate contrast by recent treatment and diagnostic methods improvement. ‎Capability for this physical severe disease and the nurses can use education, consulting and ‎supporting roles to access these goals.‎